Preoperative platelet-lymphocyte ratio is superior to neutrophil-lymphocyte ratio as a prognostic factor for soft-tissue sarcoma. Issue 1 (December 2015) - Que, Yi; Qiu, Haibo; Li, Yuanfang; Chen, Yongming; Xiao, Wei; Zhou, Zhiwei; Zhang, Xing
Abstract Background Inflammation can promote tumor growth, invasion, angiogenesis and even metastasis. Inflammatory markers have been identified as prognostic indicators in various malignances. This study compared the usefulness of platelet-lymphocyte ratio (PLR) with that of neutrophil-lymphocyte ratio (NLR) for predicting outcomes of patients who underwent radical resection for soft tissue sarcoma (STS). Methods We included 222 STS patients in this retrospective study. Kaplan-Meier curves and multivariate Cox proportional models were used to calculate overall survival (OS) and disease free survival (DFS). Results In univariate analysis, elevated PLR and NLR were both significantly associated with decreased OS. In multivariate analysis, PLR (HR: 2.60; 95 % CI: 1.17–5.74, P = 0.019) but not NLR was still identified as independent predictors of outcome. Median OS was 62 and 76 months for the high PLR and low PLR groups, respectively. High PLR and NLR were both significantly associated with shorter DFS in univariate analysis, with median DFS of 18 and 57 months in the high PLR and low PLR groups. In multivariate analysis, elevated PLR (HR: 1.77; 95 % CI: 1.05–2.97, P = 0.032) was also related to decreased DFS. Discussion Our findings provide a new and valuable clue for diagnosing and monitoring STS. Prediction of disease progression is not only determined by the use of clinical or histopathological factors including tumor grade, tumor size, and tumor site but also by host-response factors such as performance status, weight loss, and systemic inflammatory response. They also significantly affect clinical outcomes. Thus, PLR can be used to enhance clinical prognostication. Furthermore, the PLR can be assessed from peripheral blood tests that are routinely available without any other complicated expenditure, thus providing lower cost and greater convenience for the prognostication. Conclusion Elevated preoperative PLR as an independent prognostic factor is superior to NLR in predicting clinical outcome in patients with STS.